دراسة تصنيفية مورفولوجية لـتسعة أنواع تنتمي للفصيلة البوراجينية (الحمحمية ) BORAGINACEAE ضمن محافظة اللاذقية – سورية. - حداد, دينا (Latakia University Journal -Biological Sciences Series, 2019)
أكدت الدراسة التصنيفية للفصيلة البوراجينية Boraginaceae ضمن محافظة اللاذقية على وجود 9 أنواع تنتمي لها وهي : Cynoglossum creticum Mill. Onosma roussaei DC.,, Echium glomeratum Poir., angustifolium Mill. Echium, Anchusa azurea Mill ., Anchusa strigosa Labill ., Nonea obtusifolia ( Willd.) DC., Nonea palmyrensis ( Post) Sam. , Alkanna tinctoria Tausch . ، تم تصنيف العينات بالاعتماد على الصفات المورفولوجية للزهرة وتضمنت: شكل ولون التويج، الحراشف، النورات، الأوراق ونمط الأشواك، المياسم، المآبر وتوضعها ضمن الأنبوبة التويجية، الثمار، و أكدت دراسة مورفولوجية حبات الطلع أنها ذات أبعاد مختلفة وتملك نمطين: متطاول (مثلثي إجاصي) عند الأنواع (O.roussaei +E.glomeratum+ E.angustifolium+ ( A.tinctoria ومتطاول (بيضوي الى مستطيل) عند الأنواع ( C.creticum + A.azurea +strigosa A. + N.obtusifolia+ N.palmyrensis ) وفي كلا النمطين يوجد 3 خطوط ثقوب إنتاش (3- colporate ) ما عدا النوع palmyrensis N. يملك4- 5 خطوط ثقوب انتاش ( colporate4-5)، والنوع C. creticum يملك ثلاثة خطوط انتاش فقط (Tricolpate). This taxonomic study of Boraginaceae family in the governorate of Lattakia has confirmed the existence of 9 species: Cynoglossum creticum Mill., Onosma roussaei DC., Echium glomeratum Poir., Echium angustifolium Mill., Anchusa azurea Mill., Anchusa strigosa Labill ., Nonea obtusifolia ( Willd.) DC., Nonea palmyrensis ( Post) Sam., Alkanna tinctoria Tausch. Species were classified based on the morphological properties of flower which comprised: shape and colour of corolla, scales, the inflorescence, leaves and type of hairs, the stigma, the form of anthers and their positions inside the corolla tube, and the fruits. The morphological study has confirmed that pollens are of various dimensions and in two forms : The first is a longitudinal form (triangular) for species (O. roussaei + E. angustifolium + A. tinctoria ) and the second one is of a longitudinal form (oval to rectangular) for species ) C. creticum + A.azurea + A.strigosa+N.obtusifolia+ N.palmyrensis ). In both species there exist (3- colporate) except the species of N.palmyrensis which has ( colporate4- 5) and the species (C.creticum) that has only (Tricolpate(.